Development of an analytical model for predicting the lateral bearing capacity of caisson foundations in cohesionless soils. (15th December 2020) - Faizi, Koohyar; Faramarzi, Asaad; Dirar, Samir; Chapman, David
Abstract: In recent years, caisson foundations are being increasingly used as alternative foundations for supporting offshore renewable energy structures. In general, caisson foundations for offshore wind turbines (OWTs) are subjected to combined loadings including lateral, vertical and overturning moments. To guarantee the normal operation of OWTs and reduce uncertainty in the design of OWT foundations, the response to horizontal loading must be accurately estimated. This paper presents a closed-form model to estimate the lateral bearing capacity of caisson foundations for OWTs. To understand the behaviour of caisson foundations under lateral loading, and to derive the necessary parameters and relationships to build the closed-form model, a series of laboratory tests (both 1g and centrifuge) as well as numerical simulations were conducted. Field and laboratory data from the published literature were used to validate the proposed model. The proposed solution has shown to provide a better estimate of the lateral bearing capacity of caissons compared to existing models. The model is capable of predicting the lateral bearing capacity of caissons with aspect ratios less than or equal to 1.0 in both sandy and silty soils. Additionally, the method takes into account the effect of vertical loading on the lateral bearing capacity. Highlights: A closed-form model is proposed to estimate the lateral bearing capacity of suction caisson foundations. Field and laboratory data from the published literature are used to validate the proposed model. The model is used to predict the lateral bearing capacity of caissons in cohesionless soils. The proposed method takes into account the effect of vertical loading on the lateral bearing capacity.